UPAYA GURU TAHFIDZ DALAM MENINGKATKAN KEMAMPUAN MENGHAFAAL-QUR’AN SISWA KELAS VII DI SMP BAHRUL MAGHFIROH MALANG - Ahmad Zamroji; Muhammad Hanief; Atika Zuhrotus Sufiyana (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
Memorizing the Qur'an is a process to maintain and preserve the purity of the Qur'an which was revealed to the Prophet Muhammad by heart so that there is no falsification either in whole or in part. In guiding their students the teacher needs to seek several things in order to improve the ability to memorize the Al-Qur'an of the students he guides. SMP Bahrul Maghfiroh is one of the schools that facilitates students who are interested in memorizing the Qur'an by opening a new program, namely the tahfidz class. The focus of this research is to describe the efforts of tahfidz teachers in improving students' ability to memorize the Qur'an, to describe the supporting and inhibiting factors faced by tahfidz teachers in improving students' ability to memorize the Qur'an. This study uses a qualitative descriptive approach with the type of case study. The researcher found that the efforts made by the tahfidz teacher were to analyze abilities, provide motivation and memorization tasks and punishments, muroja'ah, and use methods. Supporting factors include special time, Qur'an Reading House facilities, food supplements, learning systems and facilities.Inhibiting factors include the lack of student understanding and correct pronunciation of makhorijul letters, changing student conditions, limited time and different student backgrounds.